1995
DOI: 10.1016/0169-5150(94)00020-3
|View full text |Cite
|
Sign up to set email alerts
|

Price expectations of sheep and goats by producers and intermediaries in Quetta market, Pakistan

Abstract: Analysis of producers' and intermediaries' livestock price expectations was used to describe the market in Quetta, the largest livestock market in the highlands of Balochistan Province, Pakistan, and to identify factors that determine price expectations of small ruminants. A total of 4800 expected prices for sheep and goats were collected from producers and market intermediaries at monthly intervals between January 1991 and December 1992. In addition to the expected price of the animal, liveweight, species, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…With one unit increase in the live weight of goat, expected price decreased by Afs 15 per kg. Rodriguez et al, () also reported findings similar to our results that per kg live weight was negatively related to the expected prices. This is true because in the survey data, per kg price expectation for a goat weighing 7 kg was Afs 286 and for a goat weighing 42 kg, it was Afs 167.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…With one unit increase in the live weight of goat, expected price decreased by Afs 15 per kg. Rodriguez et al, () also reported findings similar to our results that per kg live weight was negatively related to the expected prices. This is true because in the survey data, per kg price expectation for a goat weighing 7 kg was Afs 286 and for a goat weighing 42 kg, it was Afs 167.…”
Section: Resultssupporting
confidence: 91%
“…The price agreed by producers and buyers depends on their knowledge of market supply and demand, coupled with their skills in assessing animal condition (and weight) as goats are not weighed before purchase (Bett et al, ); and their market information including their knowledge of different attributes of goats preferred by different buyers (Francis, ). Market price information generally in livestock markets in developing economies is mainly limited to personal interactions between market agents due to poor market intelligence systems (Rodriguez et al, ). In a conflict‐affected country like Afghanistan, one cannot expect to have an effective market intelligence system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brorsen et al, 1984;Francis, 1990;Andargachew and Brokken, 1993;Parker, 1993;Parker and Zilberman, 1993;Williams et al, 1993;Oczkowski, 1994;Rodriguez et al, 1995). 10 The general form of the implicit price function may be written as P = F(Q,C) + e where P is the observed price of the product, Q is a set of qualitative (discrete) variables or factors each with more than one category, C is a set of quantitative variables (covariates), and e is an error term.…”
Section: Implicit Price Analysismentioning
confidence: 99%
“…This means that only products are differentiated, while the markets, buyers and sellers are not. In most empirical studies, however, linear regression models have been used with product as well as market and market agent attributes as variables implying the existence of elements of non-competitiveness in the relevant product market being investigated (Brorsen et al 1984;Francis, 1990;Andargachew and Brokken, 1993;Parker, 1993;Parker and Zilberman, 1993;Williams et al 1993;Oczkowski, 1994;Rodriguez et al 1995). While the hedonic method has been criticised for its assumptions, its inability to capture off-site benefits and difficulty in isolating marginal changes, it none the less provides a valuable tool for valuing certain types of environmental improvement and degradation (Halstead et al 1997).…”
Section: The Hedonic Price Theorymentioning
confidence: 99%